Acceptance of smallholders toward the implementation of MSPO in Felcra Seri Mendapat / Akmal Hakim Zulkifly - Zulkifly, Akmal Hakim (Faculty of Plantation and Agrotechnology, 2019)
The oil palm is the most important crop in Malaysia because its production can give profit to all parties. Sustainable oil palm is a government program that used to sustain the oil palm without harming the environment. In this study, researcher was decided to study about smallholders’ acceptance towards implementation of Malaysian Sustainable Palm Oil (MSPO). The objective of this survey is to study relationship between a few factors which is the independent variables such as experience, knowledge, attitude, technology enhancement and training with the acceptance of smallholders towards implementation of MSPO as the dependent variables. The population size of this study is about 225 smallholders which is independent smallholders is consist of 150 smallholders and dependent smallholders consist of 75 smallholders. For this case, the study was made for dependent smallholders only. Therefore, the researcher needs only 63 samples from 75 samples to analyzed based on Krejcie and Morgan table. The questionnaires will be use to collect data which the questionnaire will be distribute to dependent smallholders. The higher correlation among the factors is knowledge (0.530), attitude (0.601) and training (0.469). The most dominant factors that influence the acceptance of smallholders towards the implementation of MSPO is knowledge, attitude and training. Finding of this study had shown that the smallholder’s acceptance towards the independent variables for this research (R²) is 53.9% and the rest 46.1% were not included in this research.